As transversalidades da clínica ampliada: uma cartografia no NASF-AB. - Barros, Adriano de Sousa (2021)
The Extended Clinic emerges in the field of public health policies aiming to strengthen the doctrinal principles of the Unified Health System - SUS, being operated by the Extended Family Health and Primary Care Center) (NASF-AB), a support team for the Family’s Health Strategy – ESF, with a focus on interdisciplinary interventions, matrix support and territorial acting. This clinical model reinforces the integrality of care, having a history marked by macro, me and micropolitical crossings, which made its performance powerful and diffuse at the same time. Based on this issue, the research that supported this thesis aimed to reproduce the psychosocial practices developed by psychologists (them) in the Domain of the extended clinic. As specific objectives it was intended: to outline the psychosocial practices developed by psychology in the multidisciplinary teams of the Center; identify possible tensions generated between the biomedical paradigm and the psychosocial perspective covered by the Extended Clinic; characterize the lines that cross the experience of the Extended Clinic at NASF-AB; present clues, possibilities and limits of psychosocial practices developed by psychology within the NASF. Our methodological trajectory is based on the qualitative bias of the Cartographic Approach, using semi-structured interviews and field diaries as resources to access the experiences of participating psychologists, having as locus the NASF-AB of the cities of Campina Grande and João Pessoa, in Paraíba. The experiences of the participants and the observations of the field diary revealed similarities and differences from the modus operandi expected by psychosocial practices, mainstreamed by hard and flexible lines, which both reproduce the “common place” of the biomedical intervention, as well as failures capable of producing Space Powers that give way to the integrality of health in the territorial sphere. The results point to an expanded clinic mainstreamed by instituted and instituting forces, with psychosocial practices carried out by psychology sometimes enhanced, but which, in general, are weakened in its role as health promoters, considering actions of deterritorialization and deviation of function. Finally, the thesis contributed to problematize the agencies suffered by the expanded clinic operated by the NASF-AB, directly impacting the construction of comprehensiveness in Primary Care, which can also trigger problems in medium and high complexity services, harming the most vulnerable. This movement, reinforced by the scrapping of the Center promoted by a necropolitics resulting from the crisis that has been devastating Brazil in recent years. Psychology, in this context, can lose an important space of action, considering its participation in the teams of the Center, a situation that exposes the impact of political setbacks that fully affect professionals, services and users. More than ever, understanding the mechanisms that move this biopolitics serve as ammunition in the struggle for citizenship, a resistance movement that is strengthened by critical academic production.